Dihydrogen Splitting Using Dialkylsilylene‐Based Frustrated Lewis Pairs. Issue 11 (1st March 2017) - Dong, Zhaowen; Li, Zhifang; Liu, Xupeng; Yan, Chenting; Wei, Ningka; Kira, Mitsuo; Müller, Thomas
Abstract: Isolable dialkylsilylene5 reacts with dihydrogen in the presence of a small amount of a conventional Lewis acid (BPh3, BEt3 ) or a base (PPh3, PEt3, NPh3, NEt3 ) at low temperatures in a hydrocarbon solvent, giving the corresponding dihydrosilane10 in high yields. Both5 /Lewis acid and Lewis base/5 pairs work as a frustrated Lewis pair (FLP) to split dihydrogen, being in accord with the amphoteric nature of silylene5 . Abstract : Splitting up based on frustration : Amphoteric dialkylsilylene5 that forms frustrated Lewis pairs (FLPs) with either a Lewis acid or base splits dihydrogen at low temperatures in hexane giving the corresponding dihydrosilane10 in high yields.